CAKUPAN PENYULUHAN KESEHATAN MENGENAI DEMAM BERDARAH DENGUE PADA MASYARAKAT KABUPATEN OGAN KOMERING ULU - Yahya, Yahya; Budianto, Anif; Taviv, Yulian (Publikasi Penelitian Terapan dan Kebijakan, 2014)
Dengue hemorrhagic fever (DHF) is still becoming global public health problem and cause of outbreaks and death. One of the government's efforts to increase community’s participation in dengue control is the health promotion activities regarding DHF. This research was aimed to know the coverage of the community who have received counseling regarding DHF in Ogan Komering Ulu districts. This reseach design was an observational using cross-sectional method. The samples was taken using purposive sampling method. Results of interviews with 2,978 respondents showed that only 45.2% (1,345 respondents) who have seen/heard about DHF counseling. A total of 1,032 respondents heard outreach through television (76.7%). Only 512 people (38%) who said that they had to obtain counseling directly and only 77.9% of the 512 people, obtain counseling by health personnel. All respondents in Batu Putih Village states have never heard about counseling regarding DHF. While in the Laya Village, 85% of respondents claimed to have seen/heard counseling regarding DHF. To break the chain of transmission by vectors of DHF, should also be increased efforts to improve public knowledge about dengue fever through health promotion.